Design and Implementation of a Healthcare Monitoring System Based on LoRa - Hayder Fadhil Jawad; Ali Al-Askery; Adnan Hussein Ali (Journal of Techniques)
For humans to survive, scientific and technological advancements must be able to contribute to the solution of human medical issues. The design and implementation of a monitoring system for the measurement of blood oxygen saturation, heart rate, and body temperature have been combined into one tool in this study. The measurement results are shown both on the measuring instrument's OLED display and a remote monitoring system's LCD display. This instrument uses ESP32 as a Microcontroller and LoRa as a wireless communication technique. The MLX90614 sensor is used to detect body temperature, while the MAX30100 sensor is used to monitor blood oxygen saturation and heart rate. Testing Measurements are calibrated using instruments that meet industrial standards (Wincom infrared thermometer and GE patient monitor) used in the hospital. When compared to industry-standard instruments, the tool's accuracy is 98.18% for measurements of blood oxygen saturation, 96.54 % for measurements of heart rate, and 98.78 % for measurements of body temperature. The instrument's total accuracy, calculated as the average of all three factors, was 97.63 %. If the abnormalities in the recorded parameters are detected, then an alert will be triggered (buzzer and blinking LED). this instrument can help the patients to check their health status and provide remote monitoring of health providers.